Social Environment as a Factor in the Changing Values of Students Youth - I. A. Gazieva (Высшее образование в России)
This article is devoted to the study of the influence of the social environment and its changes on the values of students. The article says that ensuring adherence to values is a difficult task, including a deep study of the nature of values, the conditions for their formation, as well as the development of measures to ensure sustainable adherence to these values, especially among students. Based on various definitions of values, the article presents the author’s operational definition, which became the starting point for the organization of applied sociological research. Based on the conducted factorial and cluster analysis of the sociological research data, typological groups were formed, described through correlation with the heroes of Russian literature. Thanks to the chosen method of typological analysis, it was possible to clearly demonstrate possible changes in the values of student youth under the influence of a changing social environment, and also describes the likely social trajectories of students as a result of moving away from previous values.